Multicriteria Group Decision Making Using Fuzzy Approach for Evaluating Criteria of Electrician - Wiwien Hadikurniawati; Khabib Mustofa (Institute of Advanced Engineering and Science, 2016)
This paper presents an approach of fuzzy multicriteria group decision making in determining alternatives to solve the selection problem of the electrician through a competency test. Fuzzy approach is used to determine the highest priority of alternative electrician who has knowledge and ability that best fits the given parameters. Linguistic variables are presented by triangular fuzzy numbers. They are used to represent a subjective assessment of the decision-makers so that uncertainty and imprecision in the selection process can be minimized. Fuzzy approach require transforming crisp data to fuzzy numbers. Output of the best alternatives is generated by ranking method. Ranking has been made base on eight criteria which make the evaluation basis of each alternative. Ranking of the results is determined using different value of optimism index (). The fuzzy multi criteria decision making (FMCDM) calculation is using the best alternative using three value of optimism index. The result of calculation shows that the same alternative reached from different index of optimism. This alternative is the highest priority of decision making process.